2019
DOI: 10.1177/2394481119849272
|View full text |Cite
|
Sign up to set email alerts
|

Right to Education Act: Universalisation or Entrenched Exclusion?

Abstract: Right to Education (RTE) Act is intended to provide free and compulsory elementary education to all children aged 6–14 years. This article examines key constituents of elementary education in view of the RTE Act such as current attendance rate, types of institutions, medium of instruction, neighbourhood schools, Monthly per capita expenditure on elementary education (MPCEE)and incentives during pre- and post-RTE period using National Sample Survey Organisation’s 64th (2007–2008) and 71st (2014) round of unit l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Increase in disbursement of subsidised food grain benefits from PDS and ICDS played a crucial role for this improvement which was also highlighted by Bhaskar (2011), Himanshu (2013), Himanshu and Sen (2013), IDFC (2013) and Jha and Acharya, (2016) as well. Considerable upliftment in the school enrolment and school attendance has been observed too during this period due to the implementation of MDM programme (De et al 2011;ASER 2013;Jayaraman and Simroth 2015), ICDS (Srivastava and Bhaskar 2011;Himanshu 2013;Himanshu and Sen 2013;IDFC 2013) and also the Right of Children for Free and Compulsory Education (RTE) Act 2009 (Kumar et al 2019) which enhanced admission and attendance together with completion of elementary education for the children of 3-14 years age group. Even the share of deprived people who had no access to electricity reduced significantly mainly due to policies taken up by the government in this regard specifically National Electricity Policy ( 2005) and National Rural Electrification Policy ( 2006) which solely aimed at providing quality and reliable power supply at reasonable rates to all households (GoI 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in disbursement of subsidised food grain benefits from PDS and ICDS played a crucial role for this improvement which was also highlighted by Bhaskar (2011), Himanshu (2013), Himanshu and Sen (2013), IDFC (2013) and Jha and Acharya, (2016) as well. Considerable upliftment in the school enrolment and school attendance has been observed too during this period due to the implementation of MDM programme (De et al 2011;ASER 2013;Jayaraman and Simroth 2015), ICDS (Srivastava and Bhaskar 2011;Himanshu 2013;Himanshu and Sen 2013;IDFC 2013) and also the Right of Children for Free and Compulsory Education (RTE) Act 2009 (Kumar et al 2019) which enhanced admission and attendance together with completion of elementary education for the children of 3-14 years age group. Even the share of deprived people who had no access to electricity reduced significantly mainly due to policies taken up by the government in this regard specifically National Electricity Policy ( 2005) and National Rural Electrification Policy ( 2006) which solely aimed at providing quality and reliable power supply at reasonable rates to all households (GoI 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Luu's (2008) interviews with Khmer children in Vietnam found that teachers could be dismissive of their ethnic language (p. 158). In South Asia, the role of caste in contemporary political, socio-cultural, economic and symbolic power is complex (Desai & Dubey, 2012), although major sociological works confirm that caste remains a significant axis of teachers' attitudes and expectations regarding marginalized learners (Kumar et al, 2019;Majumdar & Mooij, 2012;Ramachandran, 2018;Sriprakash, 2012). Studies have shown teachers in India construing first-generation Adivasi (tribal) and Dalit (lower-caste) learners and their families as 'slow' and 'backward' (Balagopalan & Subrahmanian, 2003) and teachers in Pakistan segregating children by caste and putting lower effort into teaching lower-caste students (Tamim & Haq, 2015).…”
Section: What Is the Empirical Evidence On Teacher Beliefs About Disa...mentioning
confidence: 99%
“…Another key feature of DCMs is their ability to learn deep representations of the image data, meaning that they can extract high-level features from the data by processing it through multiple layers. This allows DCMs to perform well on complex image recognition tasks [31].…”
mentioning
confidence: 99%